1988
DOI: 10.1111/j.1365-2133.1988.tb03478.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro transepidermal water loss: differences between black and white human skin

Abstract: In vivo transepidermal water loss studies are characterized by large inter-individual variability and biased by environmental effects and eccrine sweating. An in vitro technique for measuring transepidermal water loss (TEWL) was used to compare TEWL in two racial groups--blacks and whites. In both groups a significant correlation between skin temperature and increased TEWL was found (P less than 0.01). Furthermore, black skin had a significantly higher mean TEWL than white skin, corrected log TEWL 2.79 and 2.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 10 publications
2
41
1
Order By: Relevance
“…In particular, after stripping Asians showed the highest TEWL (Asians 1.7 times greater than Caucasians). 9,10 They concluded a resemblance with previous studies, 11,12 which concluded that skin permeability measured by TEWL, was higher in blacks than in Caucasians. They also concluded that Asian skin had the highest permeability among the study groups.…”
Section: Question 2: Do the Biophysical Properties Of Asian Skin Diffsupporting
confidence: 70%
“…In particular, after stripping Asians showed the highest TEWL (Asians 1.7 times greater than Caucasians). 9,10 They concluded a resemblance with previous studies, 11,12 which concluded that skin permeability measured by TEWL, was higher in blacks than in Caucasians. They also concluded that Asian skin had the highest permeability among the study groups.…”
Section: Question 2: Do the Biophysical Properties Of Asian Skin Diffsupporting
confidence: 70%
“…Most studies have demonstrated that Blacks have a greater TEWL than Whites but these have been on small numbers of subjects. For instance, Wilson et al [43] reported that TEWL was 1.1· that of Caucasians and Kompaore et al found significantly higher TEWL after tape stripping in Blacks and Asians. Others have reported the opposite on larger numbers of individuals, e.g.…”
Section: Stratum Corneum Barrier Functionmentioning
confidence: 99%
“…Skin surface temperature differences can contribute to the differences in TEWL. However, Wilson et al [43] measured TEWL in vitro for cadaver skin from subjects with black or white skin. In these controlled conditions black skin had a significantly higher mean TEWL compared with the skin from the white subjects.…”
Section: Stratum Corneum Barrier Functionmentioning
confidence: 99%
“…Skin surface temperature is one of the essential factors that dictate the rate of TEWL in normal skin (24,25,(28)(29)(30). In normal human skin, TEWL has been shown to increase exponentially with skin temperature both ex vivo (31,32) and in vivo (25,30,33). A similar finding has been noted in hairless mouse skin; however, the effect is more pronounced in this species than that found in man (34).…”
Section: Discussionmentioning
confidence: 46%